Effect of Nanocoating (CuO Nanoparticles) on the Performance of Solar Evacuated Tube - Ramani, Rupeshkumar; Saparia, Anjana; Markna, Jaysukh (Journal of Sustainable Materials Processing and Management, 2022)
In domestic solar water heating solar evacuated tubes have been widely used. Enhancement of solar energy absorption is the demand of time and CuO nanoparticles onaccount of their potential uses mainly in the field of solar energy applications. Cost effective sol-gel method is applied to synthesize CuO nanoparticles on solar evacuated glasstube. The synthesizing initiated from Cupric Acetate with the colloidal solution in water. A thin film has been prepared at room temperature nearly at 30 to 38 °C. The synthesized thin film had been annealed at 300 °C for one hour to give uniform grain structure and good surface morphological properties. For the structural study,the film was characterizedbyXRD-X-Ray diffraction, SEM-Scanning Electron Microscopy& TEM-Transmission Electron Microscopy. To exhibit the optical behavior ofCuO nanoparticleson solar evacuated glass tube, UV-visible spectrum has been performed. By the calculations ofan effective mass model, the size of particles determined as 2.26 nm, which supported and justified the TEM analysis. Coated CuO nanoparticles on borosilicate evacuated glass tube has been installed as a domestic solar water heater and working satisfactorily to generatehot water. Forsolar water heatingsystem(domestic)application of nanotechnology is a novel concept. Todevelopdurable nanocoating on 1800 mm long solarevacuated borosilicate glass tube itself it was a challenge. In this research it is shown that coating is working satisfactorily with energy enhancement. This paper opens the door for new nanocoating developments opportunities.